2012
DOI: 10.1063/1.3685496
|View full text |Cite
|
Sign up to set email alerts
|

Structural dependent ultrafast electron-phonon coupling in multiferroic BiFeO3 films

Abstract: The electronic energy relaxation of polycrystalline BiFeO3 films is studied using ultrafast pump-probe spectroscopy. After photo-excitation with femtosecond laser pulses, the relaxation of hot electrons is identified to decay with two different characteristic times. The fast process is attributed to scattering of electrons with lattice-vibration modes, and the slow one is corresponding to the spin-lattice thermalization. The electron-phonon coupling is characterized by the second moment of the Eliashberg funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 31 publications
2
18
0
Order By: Relevance
“…Extracted by a bi-exponential decay function, the electron-phonon thermalization time constant has been found to be sensitive to the structure of the BFO film sample. 23 Sheu et al analyzed the subsequent slow relaxation with different optical excitation energies and found that the photo-excited electrons primarily leave the conduction band via radiative recombination. 24 Here, we concentrate on the appearance of the periodic oscillations during the slowrelaxation process.…”
mentioning
confidence: 99%
“…Extracted by a bi-exponential decay function, the electron-phonon thermalization time constant has been found to be sensitive to the structure of the BFO film sample. 23 Sheu et al analyzed the subsequent slow relaxation with different optical excitation energies and found that the photo-excited electrons primarily leave the conduction band via radiative recombination. 24 Here, we concentrate on the appearance of the periodic oscillations during the slowrelaxation process.…”
mentioning
confidence: 99%
“…28, rather than previously regarded tetragonal structure. 27,29 However, comparing with bulk BiFeO 3 with a rhombohedral structure, a slight shifting of (012) h diffraction peaks to lower 2h angles was observed, which indicates a trend of distortion toward to tetragonal structure.…”
mentioning
confidence: 99%
“…[31][32][33] The peak amplitude at zero time delay linearly depends on the number of the photoexcited electrons, as evidenced by the experiment performed at different pump fluence. 27 As shown, the DR(t)/R marked by two dashed lines in Fig. 2(a) following the initial photo-excitation.…”
mentioning
confidence: 99%
See 2 more Smart Citations